A situation of the Transcarpathian Reformed Church in the late stalinism period and its reflection in the press of the time - Ibolya Szamborovszky-Nagy; Szamborovszkyné Nagy Ibolya; Самборовскі-Нодь Ібоя; Ishtvan Chasar; Császár István; Часар Іштван (Інституті українознавства ім. І. Крип’якевича НАН України, 2022)
Abstract. The study aims at chronological and logical reconstruction of the situation the Transcarpathian Reformed (Calvinists) and the Transcarpathian Reformed Church found themselves in the period after the Soviet troops entered the region until Stalin’s death. It shows the ambivalent and at the same time chaotic situation the confession was in after the territory was annexed to the Soviet Union. Furthermore, it analyses the authorities’ narrative on the issue in the local media of the time. The narrative was the new regime’s political propaganda campaign that tried to legitimize its own ideology in the language of the region’s Reformed. Research methodology is based on the analysis of little-known and unknown archive sources of the Synodal Archives of the Reformed Church of Hungary, State Archives of the Transcarpathian Region, Central State Archives of the Highest Bodies of Power and Administration of Ukraine, State Security Service of Ukraine Administration in the Transcarpathian region, as well as recollections of participants of those events and articles in the local media. The scientifi c novelty of the paper lies in the fact that in the Ukrainian ecclesiastical history researches the problem area of the Transcarpathian Reformed was studied in a rather partial, fragmented way, touching upon separate questions, not in a chronological order, though the history of the Protestants as a collective theme, or of the Baptists as the Protestant confession with the largest organization, acquired broad attention of the researchers. The research was guided by historical chronology and covered the evolution of the Soviet regime’s anticlerical political propaganda campaign in the local media. It has been revealed that after the Soviet troops entered Transcarpathia, the church structure of the Reformed suff ered signifi cant damages; moreover, 20–25 % of the congregation’s male population was deported to the so-called three-day salvage work. The troubled situation was intensifi ed by the fact that the state registration of the Reformed was not approved by the Council for the Aff airs of Religious Cults (CARC) in 1946; instead, it wanted to assimilate the Reformed into the Evangelical Christian-Baptists’ (ECB) organization. It also turned out that in late 1946 CARC was not aware of the organizational structure, territorial division, as well as the number of believers of the Reformed. After it came to light, the community’s complete inspection was initiated followed by bureaucratic suspicion and the invitation of the KGB to help in the case of head Reformed Church pastors. After the KGB’s report the Soviet regime did not strive for the union of the Reformed and ECB, it let them be a separate confession, however this was the time when a wave of arrests of the Reformed Church pastors started. As a result, CARC wanted a man to head the Reformed who would be ready to compromise, serve the interests of the state authorities, as well as deviate from the traditional synodal-presbyter principle and organizational structure. In December 1949, Gencsy Béla was appointed head of the church. He behaved loyally (from the point of view of the state authorities) and at the same time made every eff ort to keep unregistered parishes from elimination.

Резюме. Проаналізовано й реконструйовано у хронологічному та логічному порядках стано- вище закарпатських реформатів (кальвіністів) і Закарпатської Реформатської Церкви як організації в період від захоплення краю Радянською армією до смерті Йосипа Сталіна. Розкрито амбівалентну й водночас хаотичну ситуацію, у яку потрапила конфесія внаслі- док входження регіону до складу Радянського Союзу, а також проаналізовано наративи влади щодо цього питання в тогочасній місцевій пресі, де в початковий період політич- но-пропагандивної кампанії нової влади були спроби мовою реформатів краю досягти легітимізації провладної ідеології. Проаналізовано маловідомі й невідомі архівні джерела Синодського архіву Угорської Реформатської Церкви, Державного архіву Закарпатської обл., Центрального державного архіву вищих органів влади та управління України, Архіву Управління Служби безпеки України в Закарпатській обл., а також спогади учасників тих подій і публікації тогочасної місцевої преси. Зазначено, що наукова новизна роботи полягає у тому, що в українських дослі- дженнях історії Церков проблематика закарпатських реформатів вивчалася переважно епізодично, уривчасто, розкривалися лише окремі аспекти, не у хронологічному й істо- ричному порядках, попри те, що історія протестантів загалом або ж баптистів як однієї з конфесій зокрема, яка мала найбільшу організацію, одержала досить широку увагу. Взято за провідний принцип дотримання хронології та простежено нагнітання антицерковної політичної пропагандивної кампанії радянської влади в місцевій пресі. Виснувано, що після приходу радянських військ на Закарпаття церковна структура реформатів зазнала значної шкоди, а 20–25 % чоловічого населення релігійних громад під приводом участі у триденних примусових відновлювальних роботах депортували. Зазначено, що ситуацію погіршувало й те, що державну реєстрацію реформатів у 1946 р. Рада у справах релігійних культів (РСРК) не дозволила, натомість мала намір об’єднати їх з організацією Євангельських християн-баптистів (ЄХБ). Виявлено, що наприкінці 1946 р. РСРК не володіла інформацією ні про організаційну структуру реформатів, ні про їхній адміністративний поділ, ні навіть про чисельність вірних. З’ясовано, коли влада це усвідомила, то запустила процес повного аналізу конфесії, але через недовіру до бюрократії до вивчення керівного складу реформатських священників залучили КДБ. Проаналізовано, як після доповіді КДБ радянський державний механізм відмовився від ідеї об’єднати реформатів із ЄХБ, залишив їх як окрему конфесію, одночасно розпочав- ши хвилю масових арештів реформатського духовенства. Також виявилено, що РСРК хотіло бачити на чолі реформатів людину не просто готову до компромісів, а таку, що служитиме інтересам влади й відмовиться від традиційного принципу синоду-пробстів та узвичаєної організаційної структури. Встановлено, що після того, як це відбулося у грудні 1949 р., в особі Бейли Генчі (Béla Gencsy) на чолі Церкви опинився лояльний (із погляду влади) керівник, який прагнув урятувати релігійну спільноту, що не отримала державної реєстрації, від розпуску.
Становище Закарпатської Реформатської Церкви в період пізнього сталінізму та його відображення у тогочасній пресі
Keywords: Transcarpathia Oblast; Transcarpathian Reformed Church; Сhurch history; Soviet regime; the Reformed (Calvinists); Закарпатська область; Закарпатська Реформатська Церква; історія Церкви; радянська влада; реформати (кальвіністи)